2008
DOI: 10.2478/s11772-008-0013-4
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric measurements of new antiferroelectric liquid crystals

Abstract: Three new pure antiferroelectric materials, synthesized at the Military University of Technology (MUT), were investigated by dielectric means. Clear relaxation modes were detected, i.e., Soft, Goldstone, low frequency in-phase (PL) as well high frequency anti-phase (PH) modes for paraelectric Sm A*phase, ferroelectric Sm C* phase and antiferroelectric Sm CA* phase, respectively. Additionally, a high relaxation mode in Sm CA* was found. The relaxation frequencies fR of the observed modes were calculated from Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 5 publications
0
9
1
Order By: Relevance
“…The increase in GM strength in the SmC * phase in comparison to that in the SmC* phase was previously reported by Uehara et al [30] and Lagerwall et al [31]. Therefore, from the above considerations, we can identify the range from 92.0 to 78.6 C as a new phase and that can be identified as the SmC * phase which is extremely sensitive with respect to the cell conditions, aligning material, etc., and which did not appear in earlier studies [9] in a 5-mm cell due to the suppression of this phase in thin cells. Three dielectric modes are observed in this phase, two in the low frequency region and another one in the high frequency region (Figure 4(b)).…”
Section: Dielectric Studiescontrasting
confidence: 42%
See 2 more Smart Citations
“…The increase in GM strength in the SmC * phase in comparison to that in the SmC* phase was previously reported by Uehara et al [30] and Lagerwall et al [31]. Therefore, from the above considerations, we can identify the range from 92.0 to 78.6 C as a new phase and that can be identified as the SmC * phase which is extremely sensitive with respect to the cell conditions, aligning material, etc., and which did not appear in earlier studies [9] in a 5-mm cell due to the suppression of this phase in thin cells. Three dielectric modes are observed in this phase, two in the low frequency region and another one in the high frequency region (Figure 4(b)).…”
Section: Dielectric Studiescontrasting
confidence: 42%
“…This should be the Goldstone-like mode in the SmC A * phase and reveals the coexistence of ferroelectric and antiferroelectric orders [19] in the low-temperature phase. In an earlier study of this material, Perkowski et al [9] identified this mode as P L . They denoted the highest frequency (,106 Hz) mode as the X mode and the mode around 105 Hz as the P H mode in the SmCA* phase.…”
Section: Dielectric Studiesmentioning
confidence: 95%
See 1 more Smart Citation
“…From Fig. 9 one can conclude that P H mode is stronger under DC field (when of course SmC A * exists) [7,8]. Below 60 • C the BIAS field does not affect the SmC A * phase at all.…”
Section: Dielectric Behavior Of Antiferroelectric Phasementioning
confidence: 82%
“…The orthoconic antiferroelectric compounds of the homologous series 4'-(1-methylheptyloxycarbonyl) biphenyl-4-yl 4-[(4,4,4,3,3,2,2-heptafluorobutoxy)alk-1-oxy 2-fluorobenzoate (3FmHPhF) were used for investigations (Scheme 1): The phase transitions were confirmed by dielectric measurements [23].…”
Section: Methodsmentioning
confidence: 99%